Edukasi Financial Management Behaviour Untuk Meningkatkan Melek Literasi Keuangan - Kamil, Islamiah; Kabdiyono, Era Agita; Parashakti, Ryani Dyan; Irawan, Indra Ade (Jurnal Pengabdian Kepada Masyarakat, 2023)
The purpose of this community service activity is to increase financial literacy in the Tidung Island community, the South Thousand Islands DKI Jakarta through Financial Management Behavior Education. The stages of activities carried out include the stages of preparation, implementation, and monitoring. Based on the community service activities that have been carried out, it can be concluded that Financial Management Behavior Education from (1) the financial knowledge dimension can be understood in terms of Financial Management Behavior knowledge. This has the meaning that the Financial Management Behavior Education service is carried out well so that it can be accepted by the participants. (2) The financial behavior dimension can also be well understood, this has the meaning that the Financial Management Behavior Education service is carried out well so that in terms of skills the participants are able to apply Financial Management Behavior in everyday life. (3) The financial attitude dimension has been well understood, this has the meaning that the Financial Management Behavior Education service is well implemented so that in terms of attitude the participants can behave carefully regarding their personal finances or company finances so that they can make financial reports each period.